2017
DOI: 10.1016/j.lungcan.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of TTF-1 expression in patients with stage IV lung adenocarcinomas

Abstract: TTF-1 expression was evaluable in 479 (75%) of all patients reviewed, and was positive in 383 (80%, 95% CI 76-83%). Clinicopathologic features were similar between TTF-1 positive and TTF-1 negative tumors, except EGFR mutations were more common in TTF-1 positive cases (24% vs 6%, p<0.001). In univariate analysis, overall survival was significantly longer in patients with TTF-1 positive versus TTF-1 negative tumors (18 months vs 9 months, p<0.0001). In multivariate analysis, TTF-1 positivity remained associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 34 publications
7
40
5
2
Order By: Relevance
“…Unlike a previous report conducted on a cohort of Asian patients that suggested that ROR1 overexpression is induced by TTF-1, [13] we did not nd any correlation between ROR1 mRNA levels and TTF-1 expression. Furthermore, in contrast to previously reports, [31][32][33] in our patient cohort TTF-1 expression was not prognostic for survival, although we acknowledge that this result could be biased by the low number of patients that we analyzed.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike a previous report conducted on a cohort of Asian patients that suggested that ROR1 overexpression is induced by TTF-1, [13] we did not nd any correlation between ROR1 mRNA levels and TTF-1 expression. Furthermore, in contrast to previously reports, [31][32][33] in our patient cohort TTF-1 expression was not prognostic for survival, although we acknowledge that this result could be biased by the low number of patients that we analyzed.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with previous studies, cases with pulmonary NMC mainly expressed keratin, P63, and/or P40 in IHC, which suggests that NMC cells are derived from squamous cell carcinoma 9,25,26 . Two patients (Cases 2 and 7) were positive for TTF-1 expression, which favoured the diagnosis of lung adenocarcinoma 27 . The signi cance of TTF-1 expression in this entity is unclear.…”
Section: Discussionmentioning
confidence: 93%
“…While Puglisi et al observed a detrimental effect of TTF-1 expression in resected NSCLC 11 , the relationship between TTF-1 and survival was not found in other observational studies 12 , 14 , 16 - 19 , 23 , 27 , 31 , 32 , 37 . However, others investigators reported that TTF-1 positivity was associated with a better prognosis 13 , 15 , 20 - 22 , 25 , 26 , 28 - 30 , 33 - 36 , 38 . These discrepant results indicate that the prognostic significance of TTF-1 in NSCLC remains controversial.…”
Section: Introductionmentioning
confidence: 94%
“…Although the role of TTF-1 as a marker for ADC in the differential diagnosis of primary lung cancers has been well documented, its prognostic significance in patients with NSCLC has still been inconclusive 11 - 36 . While Puglisi et al observed a detrimental effect of TTF-1 expression in resected NSCLC 11 , the relationship between TTF-1 and survival was not found in other observational studies 12 , 14 , 16 - 19 , 23 , 27 , 31 , 32 , 37 .…”
Section: Introductionmentioning
confidence: 99%